Cloning, sequencing and expression analysis of the gene encoding the putative RNA polymerase of African Horse sickness virus - Huismans, H. (Henk), 1942- (University of Pretoria, 2013)
Thesis (PhD (Genetics))--University of Pretoria, 2006.